Reassessing the green promise: unveiling the limited impact of national innovation systems on environmental outcomes - Brás, G. (Journal of Cleaner Production, 2026)
This letter critically examines Fernandes et al.'s (2022) study on national innovation systems (NIS) and environmental performance. Building on their contribution, we were motivated by their use of ordinary least squares estimators in the presence of heteroscedasticity and by their positive interpretation of the NIS influence on environmental performance to reanalyse the 2020 cross-sectional data using heteroskedasticity-consistent covariance matrix estimators. While our analysis reinforces the authors’ results, our conclusions were nuanced. We also extend Fernandes et al.'s (2022) study by disaggregating environmental performance into environmental health (EH) and ecosystem vitality (EV), providing a more refined understanding of how NIS interact with environmental outcomes. Our findings reveal a disparity in the impacts of NIS components: although NIS components like institutions, human capital, and infrastructure significantly improve EH, their positive impact on EV is limited. Market sophistication even exhibits negative effects on EH. Our analysis highlights the need for a comprehensive framework that considers the varying timescales and complexities of different environmental challenges. This framework should incorporate principles of Responsible Innovation and Responsible Research and Innovation, with the aim of stimulating further research on the intricate relationships between NIS and environmental sustainability, urging policies that prioritize transformative and ecologically aligned innovation trajectories.